Aquifer Characterization Techniques Schlumberger Methods in Water Resources Evaluation Series No. 4 - Maliva, Robert G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents an overview of techniques that are available to characterize sedimentary aquifers. Groundwater flow and solute transport are strongly affected by aquifer heterogeneity. Improved aquifer characterization can allow for a better conceptual understanding of aquifer systems, which can lead to more accurate groundwater models and successful water management solutions, such as contaminant remediation and managed aquifer recharge systems. This book has an applied perspective in that it considers the practicality of techniques for actual groundwater management and development projects in terms of costs, technical resources and expertise required, and investigation time. A discussion of the geological causes, types, and scales of aquifer heterogeneity is first provided. Aquifer characterization methods are then discussed, followed by chapters on data upscaling, groundwater modelling, and geostatistics. This book is a must for every practitioner, graduate student, or researcherdealing with aquifer characterization.
Keywords: Geology; Engineering geology; Water; Hydrology; Geology; Geoengineering; Water